1991
DOI: 10.1093/oxfordjournals.alcalc.a045103
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Patterns in a Primary Care Population

Abstract: Over a one-year period the authors administered the Diagnostic Interview Schedule to 459 randomly selected patients attending an urban general medicine practice. Alcohol abuse and alcohol dependence disorders were diagnosed as current in 12% of the patients, while 19% of the patients met criteria for a past disorder. In addition, 11% and 3%, respectively, reported a history of previous or current heavy consumption. The lifetime prevalence of alcohol consumption disorders is significantly higher in males than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The measure of drinking history was the CAGE instrument for the clinical assessment of alcohol disorders (Buchsbaum et al, 1991). The CAGE score is based on answers to four questions: "Have you ever felt you should cut down your drinking?"…”
Section: Multinomial Logit Analysis Of Drinking Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…The measure of drinking history was the CAGE instrument for the clinical assessment of alcohol disorders (Buchsbaum et al, 1991). The CAGE score is based on answers to four questions: "Have you ever felt you should cut down your drinking?"…”
Section: Multinomial Logit Analysis Of Drinking Categorymentioning
confidence: 99%
“…Item responses on the CAGE are scored 0 or 1, with a higher score indicating the presence of an alcohol problem. Although the CAGE does not provide a Diagnostic and Statistical Manual of Mental Disorder, Third Edition, Revised (American Psychiatric Association, 1987), diagnosis of alcohol abuse or dependence (Girela et al, 1994), it has been validated as a clinical screening tool (Buchsbaum et al, 1991;Chan et al, 1994;Girela et al, 1994;Mayfi eld et al, 1974;McIntosh et al, 1994). Because we used values of CAGE obtained from the baseline interview and the questions referred to behaviors that occurred at any time in the past, the CAGE score (range: 0-4) measured the person's drinking history before baseline.…”
Section: Multinomial Logit Analysis Of Drinking Categorymentioning
confidence: 99%
“…[1][2][3] In a meta-analysis of five in primary care studies the pooled prevalence of lifetime problem drinking was 19.8%. 4 Many authors have therefore suggested that GPs are well positioned to identify and manage alcohol problems.…”
Section: Introductionmentioning
confidence: 99%
“…EAVY DRINKING and alcohol abuse and/or dependence are common among primary care patients, [1][2][3] and result in considerable suffering, [4][5][6] mortality, 4,5,7,8 and economic costs. 9 The risk of alcohol-related psychosocial, legal, and economic problems increases when drinking exceeds 14 drinks a week or 5 or more drinks per occasion for men.…”
mentioning
confidence: 99%